Application of ultrasonically modified cloud point extraction method for simultaneous enrichment of cadmium and lead in sera of different types of gallstone patients - Khan, Mustafa; Kazi, Tasneem Gul; Afridi, Hasan Imran; Bilal, Muhammad; Akhtar, Asma; Ullah, Naeem; Khan, Sabir [UNESP]; Talpur, Sehrish (Elsevier, 2017)
A novel and greener ultrasonically assisted/modified cloud point extraction procedure for the simultaneous preconcentration of lead and cadmium in serum samples of different types of gallstone patients was developed. The chelates of the under study metals, formerly formed with 8-hydroxyquinoline, were extracted in the micelles of a nonionic surfactant prior to analysis by flame atomic absorption spectrometer (FAAS). After the arrival of the cloud point, the critical micellar mass produced was homogenously dispersed in the aqueous phase with the help of ultrasound energy. The reliability of the developed procedure was tested by relative standard deviation (% RSD), which was found to be <5%. The performance of the proposed procedure was checked by applying to certified reference material and spiking standard in real samples. All the experimental parameters were optimized. The developed procedure of Um-CPE was applied successfully for the analysis of the target heavy metals in serum samples of different types of gallstone patients and referents. The higher levels of the understudy metals were observed in the patients as compared to the referents but the levels of the both metal were found to be considerably higher in patients with pigmented gallstones.
Keywords: Atomic absorption spectrometry; Cadmium; Cloud point extraction; Gallstones; Lead; Serum; Ultrasound energy